2022
DOI: 10.3390/children9030389
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Pain Management for the Pediatric Cancer Patient: A Literature Review

Abstract: This literature review examines the use of interventional treatments for pain management in pediatric cancer patients. While interventional procedures may be effective in cancer pain management, these procedures are infrequently employed in pediatric cohorts. This underutilization of interventional procedures may be supported by a deficit in randomized, controlled studies and literature regarding their role in pediatric cancer populations. Particularly because literature on the efficacy of interventional treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Underutilization of interventional approaches for pain is of concern, especially in view of our findings that highlight their analgesic efficacy as reflected by decreased PS and opioid utilization, safety, and benefits of these regional pain management interventions as efforts toward increasing QoL during EoL care for children with cancer. Our findings suggestive of underutilization of interventional pain management in pediatric oncology are consistent with those of a recent review article in pediatric oncology ( 19 ), which supported the fact that interventional approaches are typically reserved for refractory pain unresponsive to noninvasive treatment. Similarly, a review of literature from 1980 to 2012 indicated that although regional techniques are usually considered only in the limited context of failure of systemic treatments and/or intolerable medication side effects, their associated risks are often acceptable when the potential benefits are consistent with the overall goals of care ( 20 ).…”
Section: Discussionsupporting
confidence: 89%
“…Underutilization of interventional approaches for pain is of concern, especially in view of our findings that highlight their analgesic efficacy as reflected by decreased PS and opioid utilization, safety, and benefits of these regional pain management interventions as efforts toward increasing QoL during EoL care for children with cancer. Our findings suggestive of underutilization of interventional pain management in pediatric oncology are consistent with those of a recent review article in pediatric oncology ( 19 ), which supported the fact that interventional approaches are typically reserved for refractory pain unresponsive to noninvasive treatment. Similarly, a review of literature from 1980 to 2012 indicated that although regional techniques are usually considered only in the limited context of failure of systemic treatments and/or intolerable medication side effects, their associated risks are often acceptable when the potential benefits are consistent with the overall goals of care ( 20 ).…”
Section: Discussionsupporting
confidence: 89%
“…Use of interventions is typically done as a "last resort" for refractory pain nonresponsive to noninvasive therapies. 49 F I G U R E 3 Flowchart for assessment of children presenting with chronic pain after radiation therapy.…”
Section: Manag Ement Of R Adiation -Induced Chronic Painmentioning
confidence: 99%
“…The management of acute cancer-related pain in children has been extensively described, with guidelines surrounding use of opioids. 49 However, it is recognized that management of chronic pain is more complex and there is a reluctance by some parents and providers to give opioids long-term due to fear of side effects. 50 Assessing the etiology of the pain is important; with knowledge of the location of the primary tumor and the sites that have received radiotherapy, the practitioner would be better able to prescribe management tailored toward the child's needs.…”
Section: Manag Ement Of R Adiation -Induced Chronic Painmentioning
confidence: 99%
See 2 more Smart Citations